PHYSICOCHEMICAL CHARACTERISTICS AND PHARMACOLOGICAL ACTIVITY OF SACHA INCHI SEED OIL (Plukenetia volubilis L.): A LITERATURE REVIEW - Saputri, Ulan Mulyani; Irnawati, Irnawati; Sahidin, Sahidin; Arba, Muhammad; Fristiohady, Adryan (Jurnal Farmasi Sains dan Praktis, 2025)
Sacha inchi (Plukenetia volubilis L.) of the family Euphorbiaceae is native to Peruvian in the Amazon forest. SaIn seeds are known to contain a significant fatty acid such as linolenic acid (Omega-3), linoleic acid (Omega-6), and oleic acid (Omega-9). Several studies have shown the benefits of Sacha inchi (SaIn) for various pharmacological activities based on its compound content. The aim of this review article is to provide information about pharmacological activities and describe the physicochemical characteristics of SaIn seed oil. The method used to make this article review is a literature study gathered from national and international journals published in the last ten years through Google Scholar, NCBI-Pubmed, and Crossref with search keys in the form "Plukenetia volubilis L.", "Sacha inchi", "pharmacological activity of Sacha inchi", "physicochemical characteristics of Sacha inchi". Based on the literature review, it was found that the physicochemical characteristics of SaIn seed oil with the observed parameters of peroxide value, iodine number, saponification number and acid number showed different values depending on the extraction method used. SaIn has pharmacological activities as antioxidant, anticancer, antidiabetic, antiobesity, anticonvulsant, anti-aging, antihyperlipidemia, antibacterial and potential for alzheimer therapy.